2016
DOI: 10.1038/mi.2016.13
|View full text |Cite
|
Sign up to set email alerts
|

The mycotoxin deoxynivalenol facilitates allergic sensitization to whey in mice

Abstract: Intestinal epithelial stress or damage may contribute to allergic sensitization against certain food antigens. Hence, the present study investigated whether impairment of intestinal barrier integrity by the mycotoxin deoxynivalenol (DON) contributes to the development of whey-induced food allergy in a murine model. C3H/HeOuJ mice, orally exposed to DON plus whey once a week for 5 consecutive weeks, showed whey-specific IgG1 and IgE in serum and an acute allergic skin response upon intradermal whey challenge, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 31 publications
2
41
1
1
Order By: Relevance
“…Increased knowledge on the mechanisms on how adjuvants, including model allergens like CT, contribute to allergy development may open avenues for the identification of compounds (relevant for human exposure) with similar mechanisms of action. Few adjuvants relevant for humans have been identified in animal models, but include the mycotoxin deoxynivalenol (DON) [28]. CT has previously been reported to affect the bacterial composition in the gut, but with no profound effects on the Clostridia strains [44], the strains mostly affected in the present study.…”
Section: Discussionmentioning
confidence: 42%
“…Increased knowledge on the mechanisms on how adjuvants, including model allergens like CT, contribute to allergy development may open avenues for the identification of compounds (relevant for human exposure) with similar mechanisms of action. Few adjuvants relevant for humans have been identified in animal models, but include the mycotoxin deoxynivalenol (DON) [28]. CT has previously been reported to affect the bacterial composition in the gut, but with no profound effects on the Clostridia strains [44], the strains mostly affected in the present study.…”
Section: Discussionmentioning
confidence: 42%
“…The epithelium is crucial for the initiation and orchestration of immune responses leading to sensitization to allergens. This includes secretion of pro-allergenic cytokines such as IL-33, IL-25, and TSLP [14,36]. In this study, we found that depending on the location in the intestine, IL-33, IL-25, and TSLP mRNA were increased after administration of Act d 1.…”
Section: Discussionmentioning
confidence: 53%
“…Distinct Rho proteins have been involved in the regulation of the NF-kB transcription factor, which is involved in preserving intestinal immune homeostasis and has a role in the development of inflammatory intestinal diseases [11,12]. Activation of the NF-kB signaling pathway and release of epithelium-derived IL-33, TSLP, and IL-25 are observed in airway epithelium during the initiation of type 2 immune response in respiratory mucosa [13] and in food allergy [14]. The above would suggest that there is a direct link between TJ functionality, NF-kB, and sensitization.…”
Section: Introductionmentioning
confidence: 99%
“…However, even at such low food concentrations, the effects of DON on intestinal barrier integrity remain of concern, as this might result in chronic inflammatory disease, including inflammatory bowel disease in humans, and in an increased allergic response to certain food allergens. This is of particular importance, as our group already demonstrated that DON increased the risk of whey allergy [13]. …”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, DON can increase the paracellular transport of luminal antigens and even pathogens in vitro and in vivo [10,11,12], and in humans DON may even stimulate the development of allergies, including whey allergy as demonstrated in a murine model [13]. …”
Section: Introductionmentioning
confidence: 99%